Respiratory Function and Physical Capacity in Combustible Cigarettes and Heated Tobacco Products Users: a Two-Year Follow-Up Cohort Study - Sharman, Almaz; Yermakova, Irina; Erenchina, Elmira; Tyulebekova, Gulnara; Bekzhanova, Aisulu (Global Journal of Respiratory Care, 2021)
Background: Cigarette smoking is the most common risk factor for chronic obstructive pulmonary disease (COPD), which is the fourth leading cause of death in Kazakhstan. Prior literature suggests that heated tobacco products (HTP) might be a better option for people who cannot quit smoking. The aim of this paper was to analyze the long-term effects of shifting to HTP use compared to continued combustible cigarettes (CC) use in long-term smokers. Methods: A cohort of 1200 participants (400 HTP and 800 CC) aged 40-59 years with a minimum of 10 pack-year smoking history were recruited. The functional outcomes compared between HTP and CC users included: (1) COPD Assessment Test (CAT); (2) post-bronchodilator lung function; (3) 6-minute walking distance (6MWD) test; and (4) metabolic syndrome components. Multivariable linear mixed models were used to test associations between health outcomes and smoking type (HTP vs. CC) over time. Results: After 24-month 188 (117 CC users and 71 HTP users) participants were lost to follow-up, while 107 (9%) participants quit smoking. The loss to follow-up was similar in both groups with 15% for CC users and 18% for HTP users. Liner mixed models showed HTP use was associated with lesser decrease in functional outcomes over time compared to CC users. Lung function decrease was significantly less in HTP users, while CAT scores, waist circumference, and systolic blood pressure were significantly better compared to CC users. Conclusion: This study demonstrated that while both CC and HTP users experienced decrease in lung function, HTP users experienced it to a significantly lesser degree, while demonstrating better CAT score and physical characteristics compared to CC users. The results of this study suggest that HTP might be a less deleterious alternative compared to CC in people with long history of CC use and who cannot quit smoking.